Learning object development for the Anatomy teaching in Nursing - Rafael Lustosa Ribeiro; Valéria Aparecida Masson; Maiza Claudia Vilela Hipolito; Lucia Tobase; Edenir Aparecida Sartorelli Tomazini; Heloisa Helena Ciqueto Peres (Rev Rene)
Objective: to describe the development of the learning object called “Disciplinary Complement of Anatomy” for the teaching and learning of Anatomy subject. Methods: this is a methodological study on the construction of the learning object to complement the studies in the subject, using the Analysis, Design, Development, Implementation and Evaluation model in the instructional design. Results: as a virtual class, the learning object was developed according to the steps of Analysis, Design, Development, Implementation, and Evaluation and it was implemented in Prezi® as a virtual environment. Conclusion: the virtual class was set up in an innovative strategy that allowed autonomy in learning and managing technologies in the educational process, articulating ethics in the study of Anatomy.